Forecast for the Number of Colonies and Honey Yield in Turkey - Nur İlkay Abacı; Samet Hasan Abacı; Selim Bıyık (Turkish Journal of Agriculture: Food Science and Technology)
According to FAOSTAT 2017 data, Turkey located ranks second after China in terms of world honey production and ranks third in terms of the number of colonies. According to Turkish Statistical Institute (TURKSTAT) 2018 data, Turkey had 7.904.502 colonies and total honey production of 107.920 tons while the average honey yield was calculated 13.7 kg per colony. It is economically important that informing to beekeepers and policymakers the expected change in the number of colonies and honey yield in the next years. This study aims to estimate the production values for the next 5 years by using the number of colonies and honey yields of the past years. For this purpose, the next five years (2019-2023) forecast has been made by using data from the last 50 years (1969-2018). ARIMA (1,1,0) first-degree autoregressive time series model was used for the number of colonies and honey yields from the data obtained from TURKSTAT and FAOSTAT. SPSS package program was used for forecasting. According to the results, compared to 2018 an increase of 1.3% and 7.4% is expected in the number of colonies between 2019 and 2023. In addition, the honey yield is expected to increase between 2.77% and 3.12% compared to 2018. It seems that increasing the number of colonies and expecting a less increase in honey yield per colony will increase the production costs in the next years. Hence, consumers will consume honey and honeybee products at a higher price. It can be suggested that, beekeepers should take care about increasing the number of colonies as well as increase the honey yield per colony to beekeeping economy, consumers and the economy of the country.